(untitled) (Journal of Nematode Morphology and Systematics, 2010)
A new species of Stegelletina, S. leopolitensis sp. n., is described from the soil around roots of steppe vegetation in the city of L’viv, Ukraine. It is closely related to S. devimucronata and S. similis with regard to the lip morphology and tail shape. It is particularly characterized by the sunken and modifi ed vulval area by which it differs from the other two species as well as from all other species of the genus. Furthermore, the new species differs from S. devimucronata in having only one digitate projection on each lip (vs two in S. devimucronata), and from S. similis in the cuticle morphology (cuticle annulation incised vs coarsely tessellated in S. similis) and in the fi ne morphology of the fi rst lip tine as counted from the primary axil (rounded vs fi nely incised in S. similis). A tabular key is provided to all known species of Stegelletina.